2020
DOI: 10.1177/0954410020965773
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of rotating detonation fueled by pre-combustion cracked kerosene under different channel widths

Abstract: In this study, the effects of channel widths on the characteristics of the rotating detonation wave (RDW) were investigated. Pre-combustion cracked kerosene and 50% oxygen-enriched air were taken as the propellant. Keeping the outer diameter ( D = 150mm) constant, the channel widths ( W) of the combustor range from 15 mm to 50 mm in the experiments. The results indicate that the time for the formation of a stable RDW is longer under the wider channel, while the velocity of the RDW increases significantly with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The effect of oxygen mass fraction (less than 40.5% to more than 43.6%) on wave propagation modes was investigated. Zhong [24,25] and Yang [26] used kerosene pre-combustion cracked gas and oxygen-enriched air (oxygen ratio of 50% and 30%) to achieve rotating detonation, and investigated the basic characteristics of the rotating detonation wave. Han et al [27] also conducted experiments on rotating detonation with kerosene-fuel-rich gas and oxygenenriched air and found that the minimum oxygen content that could successfully initiate and maintain the stable propagation of the detonation wave is 32%.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of oxygen mass fraction (less than 40.5% to more than 43.6%) on wave propagation modes was investigated. Zhong [24,25] and Yang [26] used kerosene pre-combustion cracked gas and oxygen-enriched air (oxygen ratio of 50% and 30%) to achieve rotating detonation, and investigated the basic characteristics of the rotating detonation wave. Han et al [27] also conducted experiments on rotating detonation with kerosene-fuel-rich gas and oxygenenriched air and found that the minimum oxygen content that could successfully initiate and maintain the stable propagation of the detonation wave is 32%.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (Bao-xing et al, 2021) found that the reducing combustor width leads to decreases in thrust stability. Wang et al (2020) chose pyrolytic gases of kerosene as fuel and conducted experiments in oxygen-rich air to study the influence of the equivalent ratio and nozzle configuration changes on detonation combustion. The convergence nozzle helps in increasing the propagation velocity of the detonation wave.…”
mentioning
confidence: 99%